Metal-organic frameworks as advanced sorbents for oil/water separation - Shahmirzaee, Mozhgan; Abdi, Jafar; Hemmati-Sarapardeh, Abdolhossein; Schaffie, Mahin; Ranjbar, Mohammad; Khataee, Alireza (Elsevier, 2022)
The crude oil spills have direct or indirect catastrophic damage to the ecosystem and aquatic life. Metal -organic frameworks (MOFs) have gained great attention as promising candidates for cleaning up oily pol-lutants from water. The emphasis of this review is on the recent applications of MOFs with different mor-phologies and chemical compositions, e.g., different metals, for oil/water separation. The sorption by various MOFs based on the metal element is investigated to remove oily pollutants. In addition, a com-parison of the MOF materials as a new hydrophobic platform and removal methods for oil sorption are presented. The other oil separation methods are briefly described, showing the potential of MOFs in cleaning up the crude oil spills. Moreover, the mechanism of sorption and efficiency enhancement strate-gies are highlighted and the stability of MOFs in water, as the most important feature of the sorbent, is discussed. Furthermore, the economical and practical implementation as key factors are reviewed for useful and industrial usage. The successful performance of the MOFs for the separation of oily pollutants from water is concluded to be useful for researchers to focus on it.(c) 2022 Elsevier B.V. All rights reserved.
Keywords: Metal-organic frameworks; Hydrophobic; Oil spill; Separation; Hydrocarbon; Sorption